2007
DOI: 10.1080/02699050701630342
|View full text |Cite
|
Sign up to set email alerts
|

The European Brain Injury Questionnaire (EBIQ) as a reliable outcome measure for use with people with brain injury

Abstract: It is concluded that the EBIQ is a clinically reliable measure to determine the subjective well-being of people with brain injury and to assess change of subjective concerns over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…This compares favourably with EQIB testre-test reliabilities. 58,59 The correlations with the other measures were a little low (Table 3) and suggest the QOLIBRI offers something different. The known group analysis (Table 4) suggested the QOLIBRI scales are very sensitive to common TBI sequelae.…”
Section: Discussionmentioning
confidence: 91%
“…This compares favourably with EQIB testre-test reliabilities. 58,59 The correlations with the other measures were a little low (Table 3) and suggest the QOLIBRI offers something different. The known group analysis (Table 4) suggested the QOLIBRI scales are very sensitive to common TBI sequelae.…”
Section: Discussionmentioning
confidence: 91%
“…The testretest reliability of the QOLIBRI is similar to that of the EBIQ (Sopena et al, 2007), a patient-reported outcome measure developed for TBI.…”
mentioning
confidence: 79%
“…It would meet the requirements of clinicians overwhelmed by the accumulation of measures. The QOLIBRI is reasonably short at 37 items and it is at least as easy to understand and complete as generic HRQoL tools which have been used in patients with TBI such as the SF-36 or EBIQ [13,16,66,[74][75][76]. In addition the QOLIBRI poses questions in a positive fashion, with a unidirectional 5-point response option.…”
Section: Qolibri: Clinical Use and Further Developmentmentioning
confidence: 99%
“…In contrast, for TBI-related HRQoL such condition-specific tools do not exist and clinicians and researchers have most often relied on measures which explore an individual's capacity to carry out various daily functions, such as the SF-36/Rand-36/ SF-12 [13,16,21,24,[62][63][64][65][66][67] or the European Brain Injury Questionnaire (EBIQ) [68][69][70][71][72][73][74][75][76]. Increasingly, however, the limitations of such instruments have been recognized and there has been rising interest in developing condition-specific HRQoL measures which target the characteristics of a particular population, disease or condition [12,14,15].…”
Section: A New Tbi-specific Hrqol Measurementioning
confidence: 99%